PENERAPAN MEDIA PEMBELAJARAN SLIDE BERBASIS CANVA UNTUK MENINGKATKAN MAHARAH QIRA’AH PADA SISWA KELAS VIII SMP ISLAM NUSANTARA 1 BANGUNREJO - Annisa Rohmatul Jannah; Zulhannan Zulhannan; Guntur Kesuma; Ahmad Basyori (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research was motivated by the fact that most students still experience difficulties in understanding the material because the learning media used are not yet interesting and not in line with current developments. This study aims to determine the application of Canva-based slide learning media to improve the maharah qira'ah of eighth-grade students at SMP Islam Nusantara 1 Bangunrejo. Classroom action research is the method used in this study, following the Kemmis and McTaggart model which includes two cycles. Each cycle includes the stages of planning, action implementation, observation, and reflection. Data were collected through direct observation, documentation of student activities, and interviews with class teachers. Data were analyzed using qualitative descriptive analysis. The results of the study indicate that the use of Canva-based slide media is proven to support a more structured, visual, and interactive learning process. Although in the initial stages of implementation it was not fully optimal, improvements made in the following cycles showed an increase in the quality of learning, both in terms of student engagement and comprehension of reading texts. This indicates that the effectiveness of media does not stand alone but is influenced by the strategy of its use in learning.